HUBUNGAN ANTARA EFIKASI DIRI DAN RESILIENSI DENGAN PRESTASI AKADEMIK MAHASISWA SEMESTER 2 POLITEKNIK NEGERI INDRAMAYU - Sohiburoyyan, Robieth; Itsna Hasni, Nafisah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
In the implementation of education, each university has learning outcomes that must be achieved by students graduating from the institution. To find out the predetermined learning outcomes have been achieved or not, measurable indicators are needed. One of the indicators used to measure the quality of university graduates is the achievement index achieved by students. In academic settings, many studies show that there is a positive relationship between self-efficacy and academic achievement. In addition, student academic achievement is also influenced by another aspect, namely resilience. Therefore, this research was conducted with the aim of knowing the relationship between the level of self-efficacy and resilience with academic achievement in 2nd semester students of Politeknik Negeri Indramayu. The method used in this research is a quantitative method. The sampling technique in this study was random sampling technique, with a total sample of 213 students. The results of data analysis showed that the significance score obtained was below 0.05. This means that there is a relationship between self-efficacy and resilience with academic achievement in 2nd semester students of Politeknik Negeri Indramayu. The higher the self-efficacy and resilience, the higher the academic achievement achieved. Conversely, the lower the level of self-efficacy and resilience, the lower the academic achievement.